Buying properties in Malaysia? Highlight on laws, policies and their implication on foreign land ownership - Mohamad, Nor Asiah (2007)
The laws and policies pertaining to foreign land ownership in Malaysia have seen tremendous changes for the past two decades. The reasons may be linked to economic, political and social factors. The changes, as claimed, have to be carried out to accommodate the current needs and circumstances. Nevertheless, at the same time, frequent changes would also create uncertainty and insecurity to the purchaser especially the investors. The Malaysian government has made various efforts towards becoming a developed country, trying hard to attract foreign investors to invest in the country. At the same time, a reasonable consideration must be given to the needs of its own people. Moreover, it is equally important to protect and to ensure that the people’s right shall not be sacrificed for the sake of development and especially when all the benefits will go to only a certain class of people. The history of foreign land ownership policy especially on the restrictions imposed by the laws and policies are worth noting. The legal perspectives are delineated from some important statutes such as the National Land Code, 1965, the Malay Reserve Enactments, the Malay Agricultural Settlement Act, the Aboriginal Peoples Act 1954, and also the restrictions imposed by the states since land is a state matter in Malaysia. Furthermore, some of the restrictions are traceable in the policies determined by the relevant ministries. Following this, the implication of these restrictions on foreign land ownership and also property market will be addressed.